2021
DOI: 10.11591/ijere.v10i4.21416
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of problem-solving efficacy sources on mathematics achievement

Abstract: <span>This study examined the relationship between mathematics achievement and mathematics problem-solving efficacy sources. A cluster sample of 123 first year prospective teachers of a Philippine higher education institution responded to a 30-item problem-solving efficacy scales and took the teacher-made tests in Mathematics in the Modern World course; namely, Non-Routine Problem Solving and Natures and Numbers Pattern Tracing (NRPS-NNPT), Math Language and Symbols (MLS), and Data Management (DM). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Philippine higher education institutions responding to the problem-solving success scale in their Mathematics in the Modern World course, namely, Non-Routine Problem Solving and Tracing Traits and Numbers Patterns (NRPSNNPT), Mathematical Language and Symbols (MLS), and Data Management (DM) were analyzed using Descriptive Statistics, Pearson-r and Standardized Multiple Regression. Among the four sources of problem-solving efficacy, only social persuasion significantly predicts mathematics achievement, particularly in NRPS-NNPT, MLS, and DM (Dagdag et al, 2021). Furthermore, a one-shot case study using quantitative methods aims to…”
Section: Reviewmentioning
confidence: 99%
“…Philippine higher education institutions responding to the problem-solving success scale in their Mathematics in the Modern World course, namely, Non-Routine Problem Solving and Tracing Traits and Numbers Patterns (NRPSNNPT), Mathematical Language and Symbols (MLS), and Data Management (DM) were analyzed using Descriptive Statistics, Pearson-r and Standardized Multiple Regression. Among the four sources of problem-solving efficacy, only social persuasion significantly predicts mathematics achievement, particularly in NRPS-NNPT, MLS, and DM (Dagdag et al, 2021). Furthermore, a one-shot case study using quantitative methods aims to…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, according to Dagdag et al (2021), self-efficacy beliefs strongly affect how people achieve their objectives, the level of effort they put forth, as well as their persistence in the midst of difficulties and pressure. Several research studies have demonstrated that some sources of self-efficacy are significantly correlated with mastery experiences.…”
Section: Introductionmentioning
confidence: 99%
“…It is also argued that hands-on activities are strategies in which learning is situated in the context of meaningful activity for knowledge to be used in similar situations later in life [4]. However, the shift of paradigm has called for curriculum reforms in most countries to suit the demands of the fast-growing words economy [5]. Thus, the paradigm shift should be adhered to in the context of the classroom to incorporate the instructional strategies which can enhance the development of PSS.…”
Section: Introductionmentioning
confidence: 99%
“…This is why teachers should prepare learners for lifelong learning. Besides, a problem becomes a problem if you do not know how to go about solving it [5]. If a problem has no 'surprises', and can be solved easily by routine or familiar procedures; such problem is considered to be only an exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation